Implementasi Metode Asy-Syafi’i dalam Meningkatkan Membaca Al-Qur’an di Pondok Tahfidz Al-Firdaus Serpong, Tangerang Selatan - Fadilatul Jannah; Dewi Indrawati; Lamya Hayatina (Student Scientific Creativity Journal, 2024)
His study aims to determine the implementation of the ash-shafi'i method in improving reading the Qur'an in the tahfidz al-firdaus serpong South Tangerang hut. The level of ability to read the Qur'an of the students is still stammering, and has not been fluent and has not even been able to read the Qur'an properly and correctly in accordance with the rules of tajweed science. This research the author took field research, using qualitative methods. For data collection techniques are observation, interviews, and documentation. The next steps are data reduction, data presentation, and conclusion drawing or verification. The results of the research conducted by teachers in improving reading the Qur'an in the Al-firdaus tahfidz cottage are as follows: First, the teacher divides 3 halaqahs, namely halaqah ula, wustho and Ulya, each student is divided per halaqah and adjusted to their level and given their respective musyrifah. For students who cannot read the Qur'an properly and correctly, they are at the ula level, students who can read the Qur'an are in the wustho and Ulya halaqah, secondly, the teacher conducts an evaluation every semester which is tested directly by the supervisor, the form of the test for the ula halaqah is that the teacher reads the Qur'an randomly and then the students read the verse found by the supervisor. While the evaluation for halaqah wustho and Ulya, namely through the tasmi' exam.